Books for sale : the advertising and promotion of print since the fifteenth century - Myers, Robin Ed; Harris, Michael Ed; Mandelbrote, Giles Ed (Publishing pathways., 2009)
"Study of book history focused on the promotion and advertising of printed materials. Part of Publishing Pathways series. Collection of 8 essays that look at the advertising and marketing techniques of booksellers and publishers from the 15th to the 20th century in the western world"--Provided by publisher.